The signaling pathways of selected traditional Chinese medicine prescriptions and their metabolites in the treatment of diabetic cardiomyopathy: a review - Li, Wencan; Liu, Xiang; Liu, Zheng; Xing, Qichang; Liu, Renzhu; Wu, Qinxuan; Hu, Yixiang; Zhang, Jiani (Frontiers in Pharmacology, 2024)
Diabetic cardiomyopathy (DCM) is a myocardial-specific microvascular disease caused by diabetes that affects the structure and function of the heart and is considered to be the leading cause of morbidity and death in patients with diabetes. Currently, there is no specific treatment or preventive drug for DCM, and there is an urgent need to develop new drugs to treat DCM. Traditional Chinese medicine (TCM) has rich experience in the treatment of DCM, and its characteristics of multi-target, multi-pathway, multi-component, and few side effects can effectively deal with the complexity and long-term nature of DCM. Growing evidence suggests that myocardial fibrosis, inflammation, oxidative stress, apoptosis, cardiac hypertrophy, and advanced glycation end product deposition were the main pathologic mechanisms of DCM. According to the pathological mechanism of DCM, this study revealed the potential of metabolites and prescriptions in TCM against DCM from the perspective of signaling pathways. The results showed that TGF-β/Smad, NF-κB, PI3K/AKT, Nrf2, AMPK, NLRP3, and Wnt/β-catenin signaling pathways were the key signaling pathways for TCM treatment of DCM. The aim of this study was to summarize and update the signaling pathways for TCM treatment of DCM, to screen potential targets for drug candidates against DCM, and to provide new ideas and more experimental evidence for the clinical use of TCM treatment of DCM.